Pengaruh Kualitas Produk, Harga Dan Desain Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Genio Di PT Capella Dinamik Nusantara Peunayong - Ammar Fuad (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of product quality, price, and product design on the purchasing decisions of Honda Genio motorcycles at PT Capella Dinamik Nusantara Peunayong. The research object consists of all consumers who purchased Honda Genio motorcycles at PT Capella Dinamik Nusantara Peunayong. The population in this study comprises 166 respondents, with a research sample of 62 respondents determined using the Slovin formula. The study employs an associative quantitative method. The regression formula applied is multiple linear regression. The findings indicate that both simultaneously and partially, product quality, price, and product design have a significant effect on consumer purchasing decisions for Honda Genio motorcycles at PT Capella Dinamik Nusantara Peunayong.